Void-growth computational analysis in elastic-plastic porous materials. (1st March 2022) - Bensaada, R.; Kanit, T.; Imad, A.; Almansba, M.; Saouab, A.
Abstract: This study aims to model the effective mechanical response of highly porous materials using computational homogenisation. A two-phase material is considered here in the form of a von Mises elastic-plastic matrix that includes spherical identical voids. A wide range of void volume fractions from 0.1% to 24% is investigated. The representative volume element principle is adopted to determine the effective yield surface of each case. Its representativeness is checked from a statistical point of view and the mechanical response is set for each porosity rate considering a wide range of stress triaxiality ratios. The relation between void volume fraction and stress triaxiality is discussed and an analysis based on the unit cell computation is proposed to examine the void shape evolution according to these parameters. Therefore, an improvement of the Gurson–Tvergaard–Needleman (GTN) model considering a wide range of void volume fractions is presented. The computational data are subsequently used to enhance the original GTN model. The parameter q 1 is translated as a linear function of the porosity while q 2 is kept equal to 1. This makes the model simpler and more suitable for a wide range of porous materials. Graphical abstract: Image, graphical abstract .